2016
DOI: 10.3762/bjoc.12.182
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of fluorinated azadipyrromethene complexes as acceptors for organic photovoltaics

Abstract: SummaryHomoleptic zinc(II) complexes of di(phenylacetylene)azadipyrromethene (e.g., Zn(WS3)2) are potential non-fullerene electron acceptors for organic photovoltaics. To tune their properties, fluorination of Zn(WS3)2 at various positions was investigated. Three fluorinated azadipyrromethene-based ligands were synthesized with fluorine at the para-position of the proximal and distal phenyl groups, and at the pyrrolic phenylacetylene moieties. Additionally, a CF3 moiety was added to the pyrrolic phenyl positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…46 Moreover, uorine atoms were introduced into the ancillary ligand framework affording Ir-F and Ir-F2 to chemically impart the ability to interact with Ab through hydrogen bonding, alter photophysical properties of the complexes, and enhance the molecules' biocompatibility. [49][50][51] Two water (H 2 O) molecules were incorporated as ligands to enable covalent coordination to Ab via replacement with amino acid residues of the peptide, e.g., histidine (His). 20,52,53 The four Ir(III) complexes were synthesized following previously reported procedures with modications (Scheme 1 and Fig.…”
Section: Rational Strategies For Peptide Modication Using Ir(iii) Comentioning
confidence: 99%
“…46 Moreover, uorine atoms were introduced into the ancillary ligand framework affording Ir-F and Ir-F2 to chemically impart the ability to interact with Ab through hydrogen bonding, alter photophysical properties of the complexes, and enhance the molecules' biocompatibility. [49][50][51] Two water (H 2 O) molecules were incorporated as ligands to enable covalent coordination to Ab via replacement with amino acid residues of the peptide, e.g., histidine (His). 20,52,53 The four Ir(III) complexes were synthesized following previously reported procedures with modications (Scheme 1 and Fig.…”
Section: Rational Strategies For Peptide Modication Using Ir(iii) Comentioning
confidence: 99%
“…with inverted configuration, using P3HT as the electron donor. Fluorination was found to have little effect on the optical properties of zinc(II) complexes but to be beneficial for their performances in devices, leading to an increase of PCE values, due to an increase of J sc , vs. devices made with the non‐fluorinated analogue …”
Section: Organic Fluorinated Materials For Photovoltaicsmentioning
confidence: 99%
“…These complexes tend to be amorphous, making it hard to obtain a crystal structure. The first crystal structure of a Zn­(WS3) 2 derivative published was that of the complex with fluorine at the para distal phenyls, which showed intermolecular interactions between the pyrrolic phenyls of two neighboring molecules . This suggested that the aromatic group on the pyrrolic substituent plays an important role in intermolecular π–π interactions and charge transport.…”
Section: Introductionmentioning
confidence: 99%
“…The first crystal structure of a Zn(WS3) 2 derivative published was that of the complex with fluorine at the para distal phenyls, which showed intermolecular interactions between the pyrrolic phenyls of two neighboring molecules. 16 This suggested that the aromatic group on the pyrrolic substituent plays an important role in intermolecular π−π interactions and charge transport. To test this hypothesis, the phenyl in the pyrrolic phenylethynyl groups was replaced with the larger 1-naphthyl group.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation